Validation of a novel hip arthroscopy simulator: establishing construct validity. Issue 4 (10th December 2019) - Cychosz, Christopher; Khazi, Zain M; Karam, Matthew; Duchman, Kyle; Willey, Michael; Westermann, Robert
Abstract: Hip arthroscopy (HA) is technically demanding and associated with a prolonged learning curve. Recently, arthroscopic simulators have been developed to anatomically model various joints including the knee, shoulder and hip. The purpose of this study is to validate a novel HA simulator. Twenty trainees and one sports medicine fellowship-trained orthopaedic surgeon at a single academic institution were recruited to perform a diagnostic HA procedure using the VirtaMed ArthroS hip simulator. Trainee characteristics, including level of training, general arthroscopy experience and hip specific arthroscopy experience, were gathered via questionnaire. For the purpose of this study, participants were categorized as novice (<25), intermediate (25–74) or experienced (≥75) based on the number of prior arthroscopies performed. Various performance metrics, including composite score, time and camera path length were recorded for each attempt. Metrics were analyzed categorically using ANOVA tests with significance set to P < 0.05. Composite performance score in the novice cohort was 114.5 compared with 146.4 and 151.5 in the intermediate and experienced cohorts ( P = 0.0019), respectively. Novice arthroscopists performed the simulated diagnostic arthroscopy procedure in an average time of 321 s compared with 202 s and 181 s in the intermediate and experienced cohorts ( P < 0.002), respectively. Cartilage damage and simulator safety score did not differ significantly between groups ( P = 0.775). Simulator composite score and procedure time showed strong correlation with year of training ( r = 0.65 and −0.70, respectively) and number of arthroscopies performed ( r = 0.65 and −0.72). The ArthroS hip simulator shows good construct validity and performance correlates highly with total number of arthroscopic cases reported during training.